Hubungan Manajemen Perawatan Gedung dengan Tingkat Kepuasan Penghuni: (Studi Kasus Pondok Raja Living Space) - Trisno Trisno; Tri Maryani; Aletta Dewi Maria Th; Bayu Ade Prabowo; Enik Rahayu (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of building maintenance management on resident satisfaction in Pondok Raja Living Space, a privately managed boarding house in Semarang City. The main focus of the research is the dominance of corrective maintenance systems in daily operational practices and their effectiveness in maintaining occupant comfort and satisfaction. A quantitative descriptive method with a field research approach was used to obtain primary data through an online questionnaire filled out by 16 out of 20 active residents (80% response rate) and secondary data from Google Reviews for the 2017–2025 period. The results of the analysis showed that building maintenance management was considered good (mean = 4.36; α = 0.964), while occupant satisfaction was in the very high category (mean = 4.69). The Spearman correlation test revealed a positive and significant relationship between maintenance management and occupant satisfaction (ρ = 0.621; p = 0.010). Simple regression analysis showed a maintenance management contribution of 76.3% to the variance in occupant satisfaction, indicating strong explanatory power. These findings confirm that although corrective maintenance is dominant, response speed, repair effectiveness, and consistent communication are able to maintain high satisfaction. However, long-term reliance on corrective mechanisms has the potential to lead to inefficiencies. Therefore, the integration of corrective and preventive maintenance strategies is recommended to improve cost efficiency, reduce long-term risks, and strengthen the sustainability of residential facilities.